World Heritage and tourism in a changing climate - UNESCO; Union of Concerned Scientists (USA); United Nations Environment Programme; Markham, Adam; Osipova, Elena; Lafrenz Samuels, Kathryn; Caldas, Astrid (UNESCO, 2016)
Incl. bibl.